Why have public mass shootings become more deadly? - Lankford, Adam (Criminology & public policy, 2020)
Research Public mass shootings in the United States have become substantially more deadly over time. We document this increase, offer a model to explain it, review supporting evidence for the model, and present new findings on offenders from 1966 to 2019. It appears that societal changes have led to more public mass shooters who are motivated to kill large numbers of victims for fame or attention, as well as to more shooters who have been directly influenced by previous attackers. They often spend extended time planning their attacks and are increasingly likely to acquire powerful weapons and develop specific strategies to enhance their lethality. Policy Implications New policies should be aimed at addressing the aforementioned factors. For instance, the deadliest public mass shooters' desires for fame and attention might be countered by a change in media coverage policies. Additionally, the deadliest perpetrators' lengthy planning periods have been associated with more warning signs being reported to police, so that type of information could justify denying many potential attackers access to firearms through extreme risk protection orders and red flag laws.